Avaliação de desempenho mecânico e térmico de material compósito para envoltória de habitações visando eficiência energética - Massa, Antonio Cláudio Ximenes (2018)
The research work evaluates the mechanical and thermal performance of a cementitious composite for the preparation of wrapping panels, applied to the architectural design of a prefabricated housing for tropical climate, aiming at the improvement of the thermal and energetic efficiency in the internal environments as an option to the ceramic building blocks. It studies the constructive viability and sustainability of the composite, which uses materials with known thermoisolating properties (vermiculite, expanded clay and metaculin) allied to the projective strategies of the Bioclimatic Architecture, in order to minimize the absorption and transfer of heat incident on the roofs and walls to the internal environments, seeking contributions for studies of these factors in the prefabricated construction process committed to the reduction of material waste. The research methodology is based on the ABNT bibliography and standards conducted the comparative tests for the characterization of composite materials, following a sequence of mix tests where a three-point scale was selected for weighing, axial compression and density tests , with comparative results of 59% lighter weight and 50% resistance of the parameters set for a traditional concrete Pilot trait, surpassing the results of these indicators for masonry of ceramic blocks. The thermal efficiency tests of the composite were initially performed on three series of test specimens submitted to the tests of the Hot Wire and the K 30 Conductivity Meter with coherent comparative results of resistance and thermal conductivity, followed by the molding of three wall prototypes with the respective traces for tests in a thermal chamber simulating and simultaneously recording the daytime and nighttime thermal variation on the two faces of the wall tested, with thermal efficiency results compatible with those of a ceramic block wall. Compounding the final results of weight, strength and thermal performance of the prototype walls compared to a traditional wall of ceramic blocks, the compatibility of the composite for the design of the prefabricated house was evident.